THEORETICAL BASIS OF ECOLOGICAL TOURISM DEVELOPMENT IN THE SYSTEM OF SOCIO-ECONOMIC RELATIONS - Qodirov, Aziz (Центр Научных Публикаций (buxdu.uz), 2021)
The article highlights the role and importance of ecotourism in the system of socio-economic relations. Theoretical and methodological bases of the concept of ecotourism are studied. The specific features and principles of development of ecotourism are also presented. The author's definition of the concept of ecotourism is given, and its objective necessity in the development of the national economy is studied in detail.